2011
DOI: 10.1038/hdy.2011.125
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetics of immunity and life history under different photoperiods

Abstract: Insects with complex life-cycles should optimize age and size at maturity during larval development. When inhabiting seasonal environments, organisms have limited reproductive periods and face fundamental decisions: individuals that reach maturity late in season have to either reproduce at a small size or increase their growth rates. Increasing growth rates is costly in insects because of higher juvenile mortality, decreased adult survival or increased susceptibility to parasitism by bacteria and viruses via c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…This is in agreement with most studies in insects, though high heritability estimates are sometimes found with no clear explanation (e.g. [ 71 ]). The body weight threshold for adult emergence therefore seems to be genetically canalized, leaving no genetic variance for selection to act on.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with most studies in insects, though high heritability estimates are sometimes found with no clear explanation (e.g. [ 71 ]). The body weight threshold for adult emergence therefore seems to be genetically canalized, leaving no genetic variance for selection to act on.…”
Section: Discussionsupporting
confidence: 92%
“…As maintaining good immune function is energetically costly, there is often a trade‐off between immunity and other costly traits (e.g. Schmid‐Hempel, ; Sadd & Schmid‐Hempel, ; Schulenburg et al ., ; Bascunan‐Garcia et al ., ; Valtonen et al ., ; Hammerschmidt et al ., ). Indeed, in a recent study by Krams et al .…”
Section: Discussionmentioning
confidence: 97%
“…As maintaining good immune function is energetically costly, there is often a trade-off between immunity and other costly traits (e.g. Schmid-Hempel, 2005;Sadd & Schmid-Hempel, 2009;Schulenburg et al, 2009;Bascunan-Garcia et al, 2010;Valtonen et al, 2010;Hammerschmidt et al, 2012). Indeed, in a recent study by Krams et al (2015) on the same species, a trade-off was found between immune function and growth; individuals fed on standard or high-energy diet grew faster but had weaker encapsulation response than individuals fed on low-energy diet.…”
Section: Figmentioning
confidence: 99%
“…Under the hypothesis that carotenoid storage is adaptive to fight pathogens, genetic variance and heritability for this trait might therefore be expected. Ample additive genetic variance and heritability have been found for components of the innate immune response in invertebrates . Investigating the genetic basis of carotenoid storage by measuring its heritability and estimating potential genetic correlations with components of the innate immune response as well as other life‐history traits appears of primary importance.…”
Section: Hypothesis 3: Carotenoids Storage Is Adaptive To Fight Pathomentioning
confidence: 99%